Home Ownership Loan Application Procedure (Kpr) Griya For Millenials (Gaul) At PTBank Pembangunan Jawa Barat dan Banten Tbk Kramatwatu - Defitri Defitri; Nora Asriani; Anis Izha Lutfiyani (Review of Accounting and Taxation, 2023)
Purpose - This writing is to find out how the procedure for applying for mortgages and find out what factors influence customer interest in choosing a mortgage. Design/methodology/approach - The method used in this research is descriptive qualitative research method. The techniques used in data collection where the data sources obtained are primary and secondary data. Finding - PT. The Regional Development Banks of West Java and Banten, Tbk have procedures that must be followed in applying for mortgages. In addition, PT. The Regional Development Banks of West Java and Banten, Tbk also apply the precautionary principle, this aims to minimize the risk of problem loans that can occur at any time. In the credit application procedure, there needs to be good cooperation between the bank and the debtor so that the credit application process goes well. From the results of the discussion, the procedure for applying for a mortgage at PT. West Java and Banten Regional Development Bank, Tbk The Kramatwatu Sub-Branch Office Serang - Banten is in accordance with established procedures and the bank has solutions to increase customer interest in choosing mortgage products so that the loan application process can run properly and according to procedures.